2012
DOI: 10.1007/s11999-011-2182-6
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Serum Improves Cold Preservation of Osteochondral Allografts

Abstract: Background Although several types of culture medium have been used for preservation of osteochondral allografts, the viability of chondrocytes decreases with increasing storage duration. We previously showed the University of Wisconsin solution is more suitable for graft preservation than culture medium. Questions/purposes We determined whether the addition of allogenic serum to University of Wisconsin solution increases chondrocyte survival during prolonged storage of osteochondral allografts. Methods Osteoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…To date, several growth factors have been modified with CBDs from von Willebrand factor (vWF), mammalian collagenase, and fibronectin, with the recombinant proteins displaying increased collagen‐binding activity without impacting cytokine activity. Here, the CBD derived from C. histolyticum collagenase did not modify the in vitro biological activity of bFGF, as shown by its capacity to promote periosteal mesenchymal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several growth factors have been modified with CBDs from von Willebrand factor (vWF), mammalian collagenase, and fibronectin, with the recombinant proteins displaying increased collagen‐binding activity without impacting cytokine activity. Here, the CBD derived from C. histolyticum collagenase did not modify the in vitro biological activity of bFGF, as shown by its capacity to promote periosteal mesenchymal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes in the superficial layer allow the flow of synovial fluid, leading to the formation of subchondral cysts, thus initiating the process of joint degeneration. 21 Our work had some limitations. First, there were no quantitative analyses of cell viability of the tissue studied.…”
Section: Discussionmentioning
confidence: 96%
“…Several supplemented media were evaluated for their benefits on the viability of preserved cartilaginous tissue, including dexamethasone-associated media, 19 hyaluronic acid, 20 allogeneic serum, 21 or tumor necrosis factor inhibitor α 19 and the cellular apoptosis inhibiting agent, 22 among others. The divergence in the literature between the means used, the absence of in vivo research, and the high cost of the preservation methods evaluated, make it difficult to decide on the best supplement to use in conjunction with preservation media to improve the quality of tissue stored for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Teng et al (2008) showed that adding recombinant IGF-1 and an apoptosis inhibitor called ZVAD-fmk to DMEM improved chondrocyte survival in bovine osteochondral grafts. Onuma et al (2012) observed that supplementation of University of Wisconsin solution with allogeneic serum enhanced the viability of rat osteochondral samples for 14 days. Pearsall et al (2004) had also indicated that osteochondral allografts could be refrigerated in a culture medium in temperatures ranging from 2 to 8°C maintaining 67 % of chondrocyte viability for up to 44 days prior to implantation.…”
Section: Discussionmentioning
confidence: 99%